The Effects of Curcumin on Weight Loss Among Patients With Metabolic Syndrome and Related Disorders: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Akbari, Maryam; Lankarani, Kamran B.; Tabrizi, Reza; Ghayour-Mobarhan, Majid; Peymani, Payam; Ferns, Gordon; Ghaderi, Amir; Asemi, Zatollah (Frontiers in Pharmacology, 2019)
Background and objective: The current systematic review and meta-analysis of randomized controlled trials (RCTs) was carried out to assess the influence of curcumin intake on weight among patients with metabolic syndrome and related disorders. Methods: We searched the following databases up until January 2018: MEDLINE, EMBASE, Web of Science, and Cochrane Central Register of Controlled Trials. The relevant data were extracted and evaluated for quality of the studies in accordance with the Cochrane risk of bias tool. Data were pooled using the inverse variance method and expressed as standardized mean difference (MDs) with 95% confidence intervals (95% CI). Results: Eighteen studies that comprised a total of 1645 individuals were finally included in the meta-analysis. Curcumin intake significantly reduced body mass index (BMI) (SMD -0.45; 95% CI, -0.78, -0.13; P=0.006), weight (SMD -0.33; 95% CI, -0.52, -0.14; P=0.001), waist-to-hip ratio (WHR) (SMD -0.35; 95% CI, -0.64, -0.06; P=0.01) and leptin levels (SMD -2.57; 95% CI, -2.93, -2.21; P<0.0001). We found no significant effect of curcumin intake on hip ratio (HR) (SMD -0.27; 95% CI, -0.63, 0.08; P=0.13) and adiponectin levels (SMD 1.96; 95% CI, -0.13, 4.05; P=0.06). Conclusions: Overall, we have found that curcumin intake among patients with metabolic syndrome and related disorders may be correlated with a decline in BMI, weight, WHR and leptin.